Peningkatan Kualitas Kesehatan Masyarakat Pasca Pandemik Covid-19 Melalui Pos Pelayanan Terpadu - Nurul Rizqy Safitri; Syamsuddin RS (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2022)
The existence of Posyandu in the midst of the community is a very big role, because it involves meeting the needs that are very important for the health of mothers and children. This study aims to determine the program, program implementation, and the results of the posyandu's role in improving the quality of health in RW 02 Rancaekek Kulon Village, Rancaekek District. This research is a qualitative research using descriptive research methods. The results of this study indicate that the Posyandu Sangkuriang Program in improving the quality of public health in RW 02 includes weighing, measuring height, immunization, counseling, nutrition, family planning (family planning), diarrhea, giving vitamin A, and providing supplementary food (PMT). As for the implementation of each Posyandu cadre has provided good service to all the people of RW 02 Rancaekek Kulon Village who come to Sangkuriang Posyandu according to a predetermined schedule while the results of the Sangkuriang Posyandu program are measured from the overall evaluation. Evaluation of the posyandu program is seen from all elements such as human resources, facilities, community participation